PWE-297 Improving compliance and outcomes of an enhanced recovery program (erp) within colorectal surgery – completing the cycle. (22nd June 2015) - Thomas, CF; Coyne, P; Collins, T; Holtham, S; Odair, G
Abstract : Introduction: ERP has revolutionised the post-operative care of patients undergoing elective colorectal surgery. Our trust employed a dedicated nurse specialist to interact with ward and medical staff to ensure a pre-designed pathway was followed and problems flagged early to senior support. Achieving compliance targets in a clinical environment is challenging, however our 2013 data showed how successful an ERP can be. Method: A prospective database was originally analysed from January 2012– October 2013 during which a dedicated nurse specialist was introduced. This continued throughout 2014. Results: In 2012–3 there was 245 patients with a median age of 63 years; in comparison to 106 patients with a median age of 60 years (range 24–91) in 2014. 99% of patients received correct bowel preparation, in comparison to 96% of patients previously. 61% of patients received enemas; reduced from 2013 where 86% of patients received enema prep. Most commonly performed procedure was a right hemicolectomy for malignancy, with 10% for rectal cancer. 70% of surgery was laparoscopic with 12% open; only 4.7% were created to open in comparison to 2013 where 65% were completed laparoscopically. 71% of patients underwent PCA this year; 1% greater than 2013; our current standard; with 17% receiving oral analgesia with PCA analgesia remaining the current standard in our hospital. Median length reduced from 7 days (2013) to 4 days (2014). Overall complication rate was low with 4% of patients having wound infections compared to 7% in 2013. Conclusion: The introduction of dedicated nurse specialists to care for all ERP patients can lead to high rates of compliance and appropriate management of colorectal patients. Improvements continue with time and lead to further reductions in length of stay and further cost benefits. Disclosure of interest: None Declared.